Molecular adsorbate effects on graphite–silica superlubricity: A ReaxFF investigation - Marcus C. Perovich; Luis E. Paniagua-Guerra; Qian Mao; Seong H. Kim; Adri C. T. van Duin; Bladimir Ramos-Alvarado (Friction)
Graphite has achieved widespread recognition as an effective solid lubricant due to its high functionality across diverse environmental conditions. Although superlubricity or ultra-low friction is readily observed at the graphite basal plane, it has been reported that certain adsorbates from the surrounding environment can deteriorate this friction regime. Here, we conducted a fundamental analysis on the effect of phenol, pentanol, and water adsorbates on the friction of graphite–silica interfaces using molecular dynamics simulations with the reactive force field ReaxFF. First, we evaluated three ReaxFF parameter sets optimized using friction-pertinent properties. It was observed that the force field optimization objective played a major role in the calculated tribological properties. Secondly, parameters such as normal load and motion directionality were investigated. Additionally, adsorption, and binding energy calculations were performed to expand upon the hypothesis that friction may be directly correlated to the interfacial molecular structure rather than binding energy and adsorbate commensuration with graphene. By quantitatively representing the interfacial roughness of each adsorbate, the hypothesis was confirmed by unequivocally explaining the calculated friction coefficients.